Constructing knowledge resources mastery: Exploring knowledge composition in process design – A resource-based theory perspective - Syed Amjad Hussain; Jakaria Dasan; Aamar Ilyas; Ahmed Hussain Khan (Journal of Excellence in Social Science, 2024)
The quest for knowledge resources is fundamentally rooted in the recognition of their intrinsic value. However, simply acquiring these valuable resources does not inherently guarantee their significance or transformative impact. This conceptual article investigates the pivotal role of knowledge resources within firms and examines how their integration into organizational processes can unlock their full potential. It explores the intricate dynamics of knowledge resource positioning, utilization, and interaction and how these factors collectively enhance the firm's value system. This study delves into the heterogeneous nature of knowledge resources through a comprehensive content analysis, moving beyond their inherent characteristics to understand their placement, utilization, and interaction within organizational processes. Our findings highlight the complex interplay between knowledge resources and their contribution to the firm's overall value. Despite its insightful contributions, this study is not without limitations. The conceptual nature of the research means that empirical validation is necessary to generalize the findings across different organizational contexts. Additionally, the scope of this study is limited to theoretical exploration, and future research could benefit from empirical investigations that test and refine the proposed concepts. Theoretically, this article enriches the knowledge management literature by applying the Resource-Based View (RBV) to elucidate how knowledge resources realize their potential within firm processes. Practically, it provides actionable insights for managers on effective knowledge resource management and value creation, underscoring the importance of strategic positioning and interaction of knowledge resources in organizational processes.